Exponentiated Geometric Sum

Calculus Level 2

y n ( x ) = e x × e x 2 × e x 3 × × e x n \large y_n (x) = e^x \times e^{x^2} \times e^{x^3} \times \ldots \times e^{x^n}

For some positive integer n n , let y n ( x ) y_n(x) denote function of x x as stated above.

What is the value of the limit below?

lim n d d x ( y n ( x ) ) x = 1 2 \large \lim_{n\to\infty} \left . \frac d{dx} \left ( y_n (x) \right ) \right |_{x=\frac12}

2 e 2e 3 e 3e e e 4 e 4e

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Peter Macgregor
May 14, 2015

Let's start from the well known expansion

1 1 x = 1 + x 2 + x 3 + provided x < 1 ( 1 ) \frac{1}{1-x}=1+x^2+x^3+\dots\text{ provided }|{x}|<1\dots(1)

Differentiating both sides shows that

1 ( 1 x ) 2 = 1 + 2 x + 3 x 2 + 4 x 3 ( 2 ) \frac{1}{(1-x)^2}=1+2x+3x^2+4x^3\dots(2)

Now differentiate the given expression for y n ( x ) y_n(x) using the product rule. You will get a sum of n terms whose rth term is r x r 1 y n ( x ) rx^{r-1}y_n(x) and so

d d x ( y n ( x ) ) = y n ( x ) ( 1 + 2 x + 3 x 2 + + n x n 1 ) \frac d{dx}\left(y_n(x)\right)=y_n(x)(1+2x+3x^2+\dots+nx^{n-1})

Now use the laws of exponents to write y n ( x ) y_n(x) as a single exponential, and factor the exponent to show that this

= e x ( 1 + x + x 2 + x 3 + + x n 1 ) ( ( 1 + 2 x + 3 x 2 + + n x n 1 ) =e^{x(1+x+x^2+x^3+\dots+x^{n-1})}((1+2x+3x^2+\dots+nx^{n-1})

Now let n n\rightarrow \infty and use (1) and (2) to write this as

e x 1 x ( 1 x ) 2 \frac {e^\frac{x}{1-x}}{(1-x)^2}

Finally put x = 1 2 x=\frac1{2} and this simplifies easily to 4 e \boxed{4e}

x+x2+x3+..........+xn= x(1+x+x2+ .... xn-1)= x * 1/(1-x) = x/(1-x)

i.e. y=e * (x/(1-x)) ==> dy/dx= e *(x/(1-x))

Thus lim (dy/dx)|x=1/2 = e **(1/2 / (1-1/2)) = e

Emad Ismail - 5 years, 9 months ago

it's -1/[1-x]*2 and differential of 1 is 0 not 1

poongottil devika - 4 years, 1 month ago

Could u pls explain how did u take the differentiation using product rule??

erica phillips - 3 years, 3 months ago

Great explanation. Just add an “x” term in that first line.

Entrenador Diamond - 11 months, 1 week ago

Log in to reply

Thank you; this tripped me up looking at the explanation... the first derivative didn’t look right. Now I see why 👍

Hans G - 5 months, 1 week ago
Lucas Tell Marchi
May 13, 2015

First of all, observe that

y n ( x ) = e x + x 2 + + x n = e k = 0 n x k y_{n}(x) = e^{x+x^{2}+\cdots+x^{n}} = e^{\sum _{k=0}^{n}x^{k}}

Then

d y n ( x ) d x = [ j = 1 n j x j 1 ] e k = 0 n x k = [ d d x j = 0 n x j ] e k = 0 n x k \frac{\mathrm{d} y_{n}(x)}{\mathrm{d} x} = \left [\sum _{j=1}^{n}jx^{j-1} \right ]e^{\sum _{k=0}^{n}x^{k}} = \left [ \frac{\mathrm{d} }{\mathrm{d} x}\sum _{j=0}^{n}x^{j} \right ] e^{\sum _{k=0}^{n}x^{k}}

Therefore, taking the limit

lim n d d x y n ( x ) = 1 ( 1 x ) 2 e 1 1 x 1 \lim _{n\rightarrow \infty} \frac{\mathrm{d} }{\mathrm{d} x}y_{n}(x) = \frac{1}{(1-x)^{2}} \; e^{\frac{1}{1-x}-1} [ lim n d d x y n ( x ) ] x = 1 2 = 4 e \therefore \left [\lim _{n\rightarrow \infty} \frac{\mathrm{d} }{\mathrm{d} x}y_{n}(x) \right ]_{x=\frac{1}{2}} = 4e

x+x2+x3+..........+xn= x(1+x+x2+ .... xn-1)= x * 1/(1-x) = x/(1-x)

i.e. y=e * (x/(1-x)) ==> dy/dx= e *(x/(1-x))

Thus lim (dy/dx)|x=1/2 = e **(1/2 / (1-1/2)) = e

Emad Ismail - 5 years, 9 months ago

Log in to reply

you are right but, you did not make any derivative yet.

weria pezeshkian - 4 years, 10 months ago

in your summation it should be from k=1 not from k=0

weria pezeshkian - 4 years, 10 months ago

What am I missing. e is a constant so the derivative of a constant to any power, even a variable power, is 0.

Kevin Glentworth - 4 years, 10 months ago
Travis Oliphant
Aug 5, 2017

y n ( x ) = exp ( x + x 2 + x 3 + + x n ) y_{n}\left(x\right)=\exp\left(x+x^{2}+x^{3}+\cdots+x^{n}\right) . Note that ( x + x 2 + x 3 + + x n ) ( x 1 ) = ( x n + 1 x ) \left(x+x^2+x^3+\cdots+x^n\right) \left(x-1\right) = \left(x^{n+1}-x\right) and therefore y n ( x ) = exp ( x n + 1 x x 1 ) . y_{n}\left(x\right) = \exp\left(\frac{x^{n+1}-x}{x-1}\right). Applying the quotient rule we derive that d y n ( x ) d x = exp ( x n + 1 x x 1 ) n x n + 1 ( n + 1 ) x n + 1 ( x 1 ) 2 \frac{dy_{n}\left(x\right)}{dx}=\exp\left(\frac{x^{n+1}-x}{x-1}\right)\frac{nx^{n+1}-\left(n+1\right)x^{n}+1}{\left(x-1\right)^{2}} and therefore, d y n ( x ) d x x = 1 2 = exp ( 1 2 1 n ) ( n 2 1 n ( n + 1 ) 2 2 n + 4 ) \left.\frac{dy_{n}\left(x\right)}{dx}\right|_{x=\frac{1}{2}}=\exp\left(1-2^{1-n}\right)\left(n2^{1-n}-\left(n+1\right)2^{2-n}+4\right) and as n n\rightarrow\infty we get lim n d y n ( x ) d x x = 1 2 = 4 exp ( 1 ) = 4 e \lim_{n\rightarrow\infty}\left.\frac{dy_{n}\left(x\right)}{dx}\right|_{x=\frac{1}{2}}=4\exp\left(1\right)=4e

1 pending report

Vote up reports you agree with

×

Problem Loading...

Note Loading...

Set Loading...